Genética da paisagem e conservação de populações relictuais de Araucaria angustifolia (Bertol.) Kuntze - Ferraz, Fabrina Teixeira (2022)
Araucaria angustifolia (Bert.) O. Kuntze is a gymnosperm native to South America, a keystone species for biodiversity in the Brazilian Atlantic Forest, and a critically endangered species. Southeastern Brazil is the northern limit of occurrence of A. angustifolia, where it is distributed in disjunct and relict populations in a heterogeneous, fragmented, and anthropized landscape. This study evaluates the influence of landscape on gene flow between individuals and populations of A. angustifolia at its northern limit of occurrence. Genetic parameters of diversity, differentiation, structure, distance, and historical gene flow were used as analysis variables, and environmental layers like altitude and land use. In a novel approach for A. angustifolia, a landscape resistance modeling is presented, which informed the permeability of spatial elements to gene flow. Complementarily, the potential of the landscape and the influence of 48 protected areas in conserving natural habitats and favoring the gene flow of A. angustifolia in the study region are discussed. As the main results of this research, there was evidence of high historical gene flow and high genetic diversity in the populations studied, but there is a tendency for genetic structuring in the long term. We identified that geographical distance and altitude may provide resistance to genetic exchanges of A. angustifolia, which is unfavorable to maintaining the genetic diversity of its populations in future generations. The influence of land use on the genetic exchanges of A. angustifolia may be inconclusive when only one generation of adult individuals is considered, leading to underestimation of the effect of anthropogenic changes on its genetic conservation. Therefore, we do recommend that at least one more generation of individuals be analyzed in future investigations. We observed that protected areas have been decisive in directing the anthropogenic transformations of the landscape in space and time. In addition, we realized that integrating landscape elements in the conservation planning of A. angustifolia populations can increase their effectiveness. Finally, we identified priority populations that need targeted strategies in order to reduce the risk of local extinction in the next generations. We believe that this research will expand discussions about the genetic conservation of A. angustifolia, reflecting on improving the effectiveness of conservation efforts for its populations, especially in its northern limit of occurrence.